The gene diagnosis of neurofibromatosis type I with headache as the main symptom: A case report and review of the literature - Gao, Ming; Liu, Haokun; Sun, Qiying; Yang, Guang (Frontiers in Neurology, 2022)
Neurofibromatosis type I (NF1) is an autosomal dominant condition. Some NF1 patients have atypical clinical manifestations, and genetic testing is not widely available and the types of mutations vary, so it is prone to misdiagnosis and missed diagnosis. Although headache is not included in the diagnostic criteria for NF1, the incidence of headache in NF1 patients is not low. We reported a NF1 family in which the proband presented with prominent headache and atypical clinical presentation, with only some skin pigmentation. We identified a frameshift mutation (c.1541_1542del, p. Q514Rfs*) in the NF1 gene by whole exome sequencing among this family, and the patients were diagnosed with NF1. We hope to attract clinicians' attention to these patients and improve genetic testing as soon as possible to increase the diagnosis rate.